Influence of basin characteristics on baseflow and stormflow chemistry in the Great Smoky Mountains National Park, USA. Issue 14 (24th May 2012) - Neff, Keil J.; Schwartz, John S.; Moore, Stephen E.; Kulp, Matt A.
ABSTRACT Relationships between stream chemistry and elevation, area, Anakeesta geology, soil properties, and dominant vegetation were evaluated to identify the influence of basin characteristics on baseflow and stormflow chemistry in eight streams of the Great Smoky Mountains National Park. Statistical analyses were employed to determine differences between baseflow and stormflow chemistry, and relate basin‐scale factors governing local chemical processes to stream chemistry. Following precipitation events, stream pH was reduced and aluminium concentrations increased, while the response of acid neutralizing capacity (ANC), nitrate, sulfate, and base cations varied. Several basin characteristics were highly correlated with each other, demonstrating the interrelatedness of topographical, geological, soil, and vegetative parameters. These interrelated basin factors uniquely influenced acidification response in these streams. Streams in higher‐elevation basins (>975 m) had significantly lower pH, ANC, sodium, and silicon and higher nitrate concentrations (p < 0.05). Streams in smaller basins (<10 km2) had significantly lower nitrate, sodium, magnesium, silicon, and base cation concentrations. In stormflow, streams in basins with Anakeesta geology (>10%) had significantly lower pH and sodium concentrations, and higher aluminium concentrations. Chemical and physical soil characteristics and dominant overstory vegetation in basins were more strongly correlated with baseflow and stormflow chemical constituents than topographical and geological basin factors. Saturated hydraulic conductivity, of all the soil parameters, was most related to concentrations of stormflow constituents. Basins with higher average hydraulic conductivities were associated with lower stream pH, ANC, and base cation concentrations, and higher nitrate and sulfate concentrations. These results emphasize the importance of soil and geological properties influencing stream chemistry and promote the prioritization of management strategies for aquatic resources. Copyright © 2012 John Wiley & Sons, Ltd.